Syntheses of carbocyclic aminonucleosides and (−)-epi-4′-carbocyclic puromycin: Application of palladium(0)/indium iodide-allylations and tethered aminohydroxylations - Cesario, Cara (2010)
Carbocyclic aminonucleosides and epi-4′-carbocyclic puromycin were prepared from an acylnitroso-derived hetero Diels–Alder cycloadduct. Pd(0)/InI-mediated allylations of a formyl species were used to install the 4′-hydroxymethyl group. A tethered aminohydroxylation strategy was employed to install the cis-2′,3′-aminoalcohol moiety with complete regio- and diastereocontrol.